The postcolonial sporting body : contemporary Indian investigations - Mani, Veena; Krishnamurthy, Mathangi (Research in the sociology of sport ;, 2024)
Bringing together leading as well as emerging scholars involved in research on sport and body, this volume of Research in the Sociology of Sport invokes the postcolonial sporting body to understand the long history of contemporary practices of play as well as their renewed, re-charged and re-signified animation within new conditions and contexts. Responding to an ongoing critical need for decolonisation in and through academic work related to sport in postcolonial nation-states, the dual focus of the collection is to unite a dwindling and often opaque body of scholarship on post-coloniality with the robust, exciting and cutting-edge work on the body in order to illuminate the challenges of sport studies in particular contexts and geographies, as well as possibilities for the future. Rooted in the belief that scholarship discussing postcolonial sporting bodies has a central role in the shaping of future policies and practices, The Postcolonial Sporting Body occupies the meeting point between post-coloniality, sport and body to consider the future not only of sport, but of global politics and identity in a world striving towards greater equity and decolonisation.